MOTIVASI BELAJAR MAHASISWA YANG BEKERJA DAN TIDAK PADA PROGRAM STUDI PENDIDIKAN EKONOMI - Desi Nurwanti; Sudarmono Sudarmono; Apuanor Apuanor (STKIP MUHAMMADIYAH SAMPIT, 2018)
This research was conducted to determine differences in learning motivation of student economic education program STKIP Muhammadiyah Sampit who have been working and who have not been working for academic year 2015/2016. The sampling technique used is purposive sampling. The data analysis technique used is the independent samples T-test. the independent samples t-test analysis, obtained t value of 0.918 and t_tabel by 2,001 (t_hitung 0.05), then Ho accepted, that there is no difference in learning motivation student education STKIP Muhammadiyah Sampit students who have been working and students who have not been working.